The Impact of Islamic Educational Foundations on the Success of the Educational Process - Abd, Ali Halim Shaker (Journal of Ecohumanism, 2024)
Imam Zain al-Abidin exemplified the highest ideals of the noble Muhammadian character through his interactions and commitments to those around him. His persona was that of a distinguished Islamic leader, characterized by profound intellectual prowess, integrity, and honor, along with a remarkable ability to engage and inspire others. Furthermore, he was recognized for his resilience in the face of adversity, demonstrating patience and composure when confronted with challenges. Throughout history, countries have taken pride in their accomplishments in education. The significance of education cannot be overstated, as its effects are evident in individuals—their conduct, abilities, principles, and convictions. Education not only influences the present circumstances of nations but also determines their future trajectory. Islamic educational principles empower both the individual and society more comprehensively. What are the means through which the greatest possible benefits and positive outcomes of Islamic education can be achieved? A society can only progress through the communication between generations by transferring ideas and experiences, provided that the transmission is not based on the whims and diverse behaviors of individuals. The new generation should not be left to learn by merely imitating family members or undergoing a trial-and-error approach, as both are unreliable paths that do not provide the individual or society with the essential elements of sustainability and advancement. The research problem lies in the perception of religion, and its importance in the lives of individuals and communities. It also addresses the form, nature, and manner in which Islamic education should specifically be designed. Moreover, the uniqueness of Islamic education and the particularity of its topics compel us to design a model that closely aligns with this subject and ensures its delivery in the desired manner.The importance of the current research lies in being a modest nucleus that contributes to stimulating researchers to explore the educational foundations of Islam from the Qur'an and the Sunnah of the Prophet, and to find ways that can help in solving many of the issues facing the educational process within our educational system. The current research aims to clarify the importance of Islamic religious theory and provide a comprehensive model in addition to teaching religious texts and Islamic educational foundations. It also addresses the qualifications that should be present in the educational process, along with the general principles and foundations that must be considered when transmitting knowledge to others. The research seeks to benefit from the Islamic theory in the educational process, particularly in the upbringing and socialization of generations in a way that aligns with society. The study focuses on the impact of Islamic educational foundations on the success of the educational process. The researcher reached the following conclusions: Islamic Educational Values: Islamic educational values are so comprehensive that lead to the formation of a distinguished and integrated personality. Such a personality can understand the universe and life around it, adopting a positive stance that elevates life and directs its course in the right direction. Conflict Between Islamic and Western Culture: The conflict between Islamic culture and Western culture (in its comprehensive civilizational sense) must intensify in a positive and effective direction, ultimately leading to the liberation of Islamic culture and the values emerging from it, from the influence of Western culture, which is based on principles and foundations that contradict those of Islam. The researcher, through his study, reached several recommendations and suggestions, which are as follows: Emphasizing the importance of the Prophetic Sunnah and studying its various aspects to derive the essential guiding principles that benefit individuals and society. Highlighting the necessity of focusing on Islamic heritage to ensure the proper organization of people's lives and the well-being of society. Preparing specialists in Islamic sciences who are qualified to understand the rulings of Islam in various aspects of life. Training students of Islamic studies to become teachers of Islamic education at various stages of schooling.